Determining the Legality of the Approach to Censorship of Films on the Grounds of Obscenity in Bangladesh - Shill, Prashanta Kumar; Bashar, Arafat Ibnul (Journal of Journalism and Media, 2024)
Film censorship is controversial in many nations, including Bangladesh. This document explores Bangladesh's obscenity-based cinema censorship's legality. In the age of "Netflix and Chill," where films from around the world can be seen anywhere and Virtual Private networks (VPN)s can overcome country bans, censorship has become almost irrelevant. The Bangladesh Films Censor Board must clear films shown in theaters, large screens, etc. A film may be rejected by the Board for immorality or obscenity, making it inappropriate for public screening. Films and other literary and artistic works have always been controversial for obscenity. Courts around the world struggled to define obscenity or accept cultural standards. The Bangladesh Censorship of Films Act 1963, the Rules of 1977, and the Code of 1985 define the conditions that can make a film immoral or obscene in Bangladesh. While many code phrases are confusing and obscure, requiring the Board to decide its extent, the grounds are clear. The constitutional protection of freedom of thought, conscience, and communication does not limit film exhibition by decency or morality. All civilized nations' constitutions and other international law documents acknowledge freedom of expression as a human right to a free and democratic society. Thus, cinema censorship must be examined to ensure it respects the right to free expression. This study examines whether Bangladeshi obscene film banning violates the right to free expression. The study investigates whether obscenity may be suppressed without limiting free speech. The qualitative study used secondary data, which was examined through content analysis.